Modeling of Knowledge Management Processes in IT Outsourcing Projects - Sobińska, Małgorzata (Modelowanie procesów zarządzania wiedzą w projektach outsourcingowych z zakresu IT, 2011)
The author presents the complexity of activities and tasks, related to the transfer and transformation of knowledge in IT-related outsourcing projects, in the form of graphical models and detailed account of the most important aspects of knowledge management in outsourcing projects. Core competences and organizational needs in the IT area are defined, with delineation of key personnel involved in proper management of the outsourcing relations and their respective roles in “knowledge processes”. Selected processes of knowledge and information management in IT outsourcing projects are illustrated in the form of process maps.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 187, s. 204-215
Keywords: kluczowi pracownicy; technologia informacyjna; zarządzanie wiedzą; transfer wiedzy; outsourcing; key employees; information technology (IT) industry; knowledge management; knowledge transfer